ETS2 targets ZMYND11 to inhibit thyroid cancer progression via the mTOR signaling pathway - Taipengfei Shu; Xinhua Wu; Chengqun Wei; Chaofeng Chen; Chao Shen; Yujie Huang; Jie Zhou; Liangxing Jiang; Ting Yan; Wen Shi; Liming Ma; Yan Yan; et al. (PLoS ONE, 2025)
Background Despite advancements in thyroid cancer (THCA) treatment, the prognosis for advanced cases remains poor. Cellular senescence is crucial in tumor progression, with ETS2 emerging as a key regulator. However, the role of ETS2 and its interaction with ZMYND11 in THCA is unclear. Methods Differentially expressed genes (DEGs) connected with cellular senescence were determined from The Cancer Genome Atlas (TCGA)-THCA dataset. Functional analysis, prognostic risk model, and nomogram were then performed to identify ETS2 as a hub gene. The roles of ETS2 and ZMYND11 were explored using Western blotting (WB), co-immunoprecipitation (Co-IP), and quantitative real-time polymerase chain reaction (qRT-PCR). Effects of ETS2 overexpression and knockdown of ZMYND11 on apoptosis, cell proliferation, epithelial-mesenchymal transition (EMT), and mTOR signaling were evaluated. In vivo, a xenograft model was established using Cal-62 cells with or without ETS2 overexpression to assess tumor growth and protein expression. Results ETS2 was notably downregulated in THCA, and its low expression was connected to adverse prognosis. ETS2 overexpression inhibited THCA cell invasion, migration, proliferation, and induced apoptosis. ETS2 also regulated the expression of EMT markers, indicating its role in inhibiting THCA progression. Co-IP analysis showed that ETS2 interacted with ZMYND11. Knockdown of ZMYND11 attenuated the inhibitory effect of ETS2 on THCA cell behavior and mTOR pathway regulation. In vivo, ETS2 overexpression reduced tumor growth and increased ETS2 and ZMYND11 expression in xenograft tumors. Conclusion This study identified the cellular senescence gene ETS2 as a tumor suppressor in THCA, which interacts with ZMYND11 to regulate THCA tumor progression through the mTOR pathway, thereby inhibiting cell senescence. Targeting the ETS2-ZMYND1 axis may provide new therapeutic strategies and prognostic biomarkers for THCA.